1-Pentadecene, a volatile biomarker for the detection of Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae) infested brown rice under different temperatures. (May 2022) - Tian, Xuemei; Hao, Jiarong; Wu, Fenghua; Hu, Hao; Zhou, Guoxin; Liu, Xingquan; Zhang, Tao
Abstract: Tribolium castaneum, a secondary pest that feeds on processed stored grains, can cause serious damage on stored grain. To reduce the loss of stored grain caused by pest infestation, monitoring and early detection of insects are essential. volatile compounds arising from insects or insect-infested stored products can be appropriate biomarkers. In this study, gas chromatography–mass spectrometry (HS-SPME-GC-MS) was used to qualitatively and quantitatively identify the volatile compounds of brown rice infested by T. castaneum under different temperatures (10 °C, 20 °C, 30 °C). Moreover, some characteristic volatile compounds were identified by partial least square-discrimination analysis (PLS-DA). Seventy-one volatile compounds, including 12 aldehydes, 11 alcohols, 21 esters, 10 ketones, 13 hydrocarbons and some other compounds, were detected in the brown rice samples infested by T. castaneum . Twenty-three characteristic volatile compounds, which had a variable importance in projection (VIP) more than 1, were identified by PLS-DA. Among them, 1-pentadecene was detected only in infested brown rice, can be used as a potential volatile biomarker for the presence of T. castaneum in brown rice during storage and transportation process. Graphical abstract: Image 1 Highlights: A total of 71 volatile compounds were detected in brown rice infected by T.castaneum. The content of 1-pentadecene has a positive correlation with infection temperature (10 °C, 20 °C, 30 °C). 1-pentadecene can only be detected in infested brown rice. 1-pentadecene can be used as a volatile biomarker for the detection of T.castaneum.